FACTORS THAT AFFECT ACCOUNTING INFORMATION SYSTEM PERFORMANCE AT CONSUMER GOODS COMPANIES IN MEDAN - noviani, Noviani (Asosiasi Dosen Akuntansi Indonesia, 2019)
The objective of the research was to analyze some factors which influenced the Performance Of Accounting Information System at Consumer Goods Companies in Medan. The Research used associative causal methods. The population was 287 IT Managers Of Consumer Goods In Medan, and all of them were used as the samples, using census sampling technique. The data were gathered by using questionnaires and analyzed by using multiple linear regression analysis with an SEM (Structural Equation Modeling) program. The result of the research showed that the involvement of users in the system development process, personal tecnical ability in information system, organization size, top management support, formalization of information system development, training and education program for users, and users’ satisfaction partially had significant effecton the performance of accounting information system. Simultaneously, the involvement of users in the system development process, personal technical ability in information system, organization size, top management support, formalization of information system development, training and education program for users, and users’ final satisfaction had significant effectthe performance of accounting information system.